2005
DOI: 10.1063/1.1926414
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and memory effect study of Ge nanocrystals embedded in LaAlO3 high-k dielectrics

Abstract: A floating gate memory structure utilizing Ge nanocrystals embedded in LaAlO 3 ͑LAO͒ high-k dielectric films has been fabricated by pulsed-laser deposition. A cross-sectional high-resolution transmission electron microscopy study revealed that the floating gate structure contains 5-nm-diam spherelike Ge nanocrystals embedded in amorphous LAO. A significant memory effect with a very high density of charge storage up to 2 ϫ 10 13 /cm 2 in the Ge nanocrystals and a maximum flat band voltage shift of 3.2 V have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
25
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…A previous study showed that dot size of Ge nanocrystals affected charge loss rate. 9 Our preliminary observation of the effects of Si nanocrystal dot size and density on memory characteristics shows that variation in deposition temperature results in different nanocrystal dot morphologies, and the memory characteristics of nanocrystal dots differ depending on deposition temperature. 10 These factors, therefore, should be carefully investigated to enhance memory quality.…”
Section: Introductionmentioning
confidence: 97%
“…A previous study showed that dot size of Ge nanocrystals affected charge loss rate. 9 Our preliminary observation of the effects of Si nanocrystal dot size and density on memory characteristics shows that variation in deposition temperature results in different nanocrystal dot morphologies, and the memory characteristics of nanocrystal dots differ depending on deposition temperature. 10 These factors, therefore, should be carefully investigated to enhance memory quality.…”
Section: Introductionmentioning
confidence: 97%
“…Memory devices based on Ge QDs are very promising due to a long charge retention time in the Ge QDs, faster writing/erasing times, and low operating voltages [1,2] Therefore, numerous investigations have been performed on this system, where the influence of different properties on charge trapping and retention were investigated [1][2][3][4][5]. However, the main mechanism of the charge storage is still not completely clear.…”
Section: Introductionmentioning
confidence: 99%
“…Non-volatile flash memories embedding nanocrystals (NC) are promising devices useful in computers, mobile phones or USB sticks [1,2]. The insertion of semiconducting (SC) NC in an insulating matrix requires the elaboration of complex ''oxide/SC/ oxide/Si(0 0 1)'' heterostructures and the control of the associated successive growth steps.…”
Section: Introductionmentioning
confidence: 99%